Proceedings of the 4th International Symposium on Health Research (ISHR 2019) 2020
DOI: 10.2991/ahsr.k.200215.007
|View full text |Cite
|
Sign up to set email alerts
|

Urban–Rural Disparities of Facility-Based Childbirth in Indonesia

Abstract: Equitable distribution of health services between areas is still a problem in various countries. Even in developed countries. This condition also applies to the utilization of healthcare facilities for childbirth. To analyze the urban-rural disparities of facilities-based childbirth in Indonesia. The analysis in this study uses raw data from the 2017 IDHS. With stratification and multistage random sampling, 17,769 women aged 15-49 years with live births in the last 5 years were sampled. Data were analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…The effect of information exposure that may improve mother’s knowledge about EBF was proven as one determinant of EBF success by several studies [ 17 , 21 , 28 , 29 ]. In Indonesia, urban areas tend to have better access to health services and information than rural areas, and this leads to higher coverage of health programs [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of information exposure that may improve mother’s knowledge about EBF was proven as one determinant of EBF success by several studies [ 17 , 21 , 28 , 29 ]. In Indonesia, urban areas tend to have better access to health services and information than rural areas, and this leads to higher coverage of health programs [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies often found that those who live in urban areas have access to better health services. This condition is related to better availability in urban areas [ 18 , 28 – 30 ]. Previous studies in Nigeria, Angola, Bangladesh, and Tanzania also informed that the type of residence affected the use of ANCs [ 31 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, women in urban areas who do ANC at least four times are more likely to give birth in health facilities than women in rural areas [ 18 , 19 ]. Adequate ANC visits are an effort to detect possible early complications during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Great distances make mothers think twice about visiting ANC 4 . Long distances and expensive service costs are known to be one of the barriers tothe public access to health services 5,6 .…”
Section: Introductionmentioning
confidence: 99%